Порівняльний аналіз можливостей сучасних СКУД для забезпечення мобільного доступу - Омельченко, А. Л. (ХНУРЕ, 2023)
Modern ACS offers to use a smartphone as an addition to standard plastic cards or completely replace them. The research in thesis described three real access control systems that are on the market and provide mobile access.
Keywords: мобільний доступ